2018
DOI: 10.1007/s00384-018-2987-9
|View full text |Cite
|
Sign up to set email alerts
|

Retromesenteric course of the middle colic artery—challenges and pitfalls in D3 right colectomy for cancer

Abstract: This paper therefore documents the worth-knowing behavior causing considerable confusion for the operating surgeon unaware of the abnormality and shows its concrete impact on patient-tailored surgical practice, in particular for laparoscopic D3 colectomy (including the "uncinated process first" approach).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The classification of the relationship between MCA bifurcation position and left edge of SMV has been reported [ 21 ]. In this study, we showed the patterns of intersection between the left edge of the SMV and the MCA branch and the frequency of each relationship [ 42 ]. It was suggested that the SMV could be used a landmark for sufficient and necessary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of the relationship between MCA bifurcation position and left edge of SMV has been reported [ 21 ]. In this study, we showed the patterns of intersection between the left edge of the SMV and the MCA branch and the frequency of each relationship [ 42 ]. It was suggested that the SMV could be used a landmark for sufficient and necessary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed the patterns of intersection between the left edge of the SMV and the MCA branch and the frequency of each relationship. (39) It was suggested that the SMV could be used a landmark for su cient and necessary lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%